Maternal Body Mass Index and the Course of the Labor - Seçkin, Berna; Özakşit, Gülnur; Biteker, Gül; Yüksel, Kutlugül; Ayarcan, Eda (Gynecology Obstetrics & Reproductive Medicine, 2011)
OBJECTIVE: To examine the effect of body mass index(BMI) on the progress of the labor and maternal, fetal outcome with preceding a normal pregnancy. STUDY DESIGN: A total of 96 women admitted to delivery ward with an uncomplicated pregnancy were included in this prospective study. After calculation of body mass index (BMI), patients were divided to groups as normal weight (20.0≤BMI<24.9), overweight (25.0≤BMI<29.9) and obese (30.0≤BMI). The incidence of labor complications, requirement of oxytocin augmentation, cesarean delivery and neonatal outcomes were assessed. RESULTS: There was no differences between groups in the frequency of occurence of dysfunctional labor patterns, induced labor and primary cesarean section. The increase in average weight gain during pregnancy (p=0.053) and fetal birth weight (p=0.013) was observed in the obese group. Perinatal outcome was not different amoung groups. CONCLUSION: Obese women with an uncomplicated pregnancy is not at significant risk for labor complications and adverse perinatal outcome.